(untitled) (Research, Society and Development, 2024)
This study aims to describe deaths from external causes affecting women in the state of Piauí. SINAN’s disease and injury notification forms were used as a data source, focusing on deaths from external causes from January 2013 to December 2022. The collected variables encompass sociodemographic characteristics (age, gender, skin color, education) and information about deaths from major ICD-10 groups (Transportation accidents, other external causes of accidental injury, and assaults), as well as the occurrence location (Hospital, public road, and home). The highest number of deaths occurred in 2021 with 463 fatalities. Regarding age, those aged 80 years or older prevailed, and individuals of mixed race predominated in the classification of transportation accidents, other external causes of accidental injury, and assault. The occurrence took place mainly in public spaces, followed by hospitals and homes. In summary, the conclusions point to the complexity and diversity of external causes of deaths among women, emphasizing the importance of multidisciplinary strategies, effective public policies, and specific interventions for different population groups.